Use of Mathematics in Quantitative Research - Gnawali, Yagya Prasad (Ganeshman Darpan, 2022)
The purpose of this study is to find out the relationship between quantitative research and mathematics. This is the literature reviewed article. I studied and reviewed different books, journals and articles for preparing this article. I found; without mathematics it is not possible to conduct the quantitative research. Quantitative research creates meaning through objectively uncover in the collected data. Quantitative research is good at providing information in large number of units rather than qualitative research. Similarly, Quantitative research is more reliable because of considering statistical method and it takes five big words like: theoretical, empirical, and nomothetic probabilistic, and causal.